New bi-mode gate-commutated thyristor design concept for high-current controllability and low ON-state voltage drop - Lophitis, Neophytos; Antoniou, M.; Vemulapati, U.; Arnold, M.; Nistor, I.; Vobecky, J.; Rahimo, M.; Udrea, F. (My University, 2016)
A new design approach for bi-mode gatecommutated thyristors (BGCTs) is proposed for high-current controllability and low ON-state voltage drop. Using a complex multi-cell mixed-mode simulation model which can capture the maximum controllable current (MCC) of large area devices, a failure analysis was performed to demonstrate that the new design concept can increase the MCC by about 27% at room temperature and by about 17% at 400 K while minimizing the ON-state voltage drop. The simulations depict that the improvement comes from the new approach to terminate the GCT part in the BGCT way of intertwining GCT and diode regions for reverse conducting operation.
Keywords: BGCT; Bi-mode; Full wafer modelling; Gate commutated thyristor; GCT; Maximum controllable current; MCC; Reverse conducting; Safe operating area; SOA; Thyristor